The Effect of Gembili Flour (Dioscorea esculenta L.) Substitution on Sensory Quality and Consumer Acceptance of Donuts - Salwa Salsabila; Luthfiyah Nurlaela; Lilis Sulandari; Aji Fajar Ramadhani (Universitas Negeri Padang, 2026)
Donuts are bakery products widely consumed by the public and are generally produced using wheat flour as the main ingredient. The high dependence on wheat flour encourages the utilization of local food resources as alternative raw materials, one of which is gembili flour (Dioscorea esculenta L.). This study aimed to examine the effect of gembili flour substitution on the sensory quality and consumer acceptance of donuts. The research employed a single-factor experimental design with five substitution levels: P1 (10%), P2 (20%), P3 (30%), P4 (40%), and P5 (50%). Sensory attributes evaluated included color, aroma, taste, and texture, while hedonic assessment consisted of color, aroma, taste, texture, and overall liking. The use of gembili flour influenced product characteristics due to its high starch content and the absence of gluten, which affected dough structure, elasticity, and the final texture of the donuts. Data were analyzed using One Way Analysis of Variance (ANOVA) followed by Duncan’s multiple range test at a 5% significance level. The findings indicated that the level of substitution significantly affected sensory quality and consumer acceptance. Treatments P1 and P2 achieved the highest scores and showed no significant differences for most parameters, whereas higher substitution levels tended to reduce product acceptability. Therefore, gembili flour substitution up to 10-20% is considered optimal for producing donuts with acceptable sensory quality and consumer preference.